PROGRAM KEMITRAAN MASYARAKAT DALAM PENGEMBANGAN PEMBELAJARAN BERBASIS ICT DI SMA TAMAN RAMA DENPASAR - I Ketut Suardana; I Made Surat; Putu Siti Firmani; I Made Subrata (LPPM Universitas PGRI Mahadewa Indonesia, 2022)
The times, students and teachers are required to be creative, innovative and know all the information that can be received through ICT-based learning media. The purpose of this service is to overcome the problem of lack of teacher knowledge in the development of information communication and technology (ICT)-based learning media. Activities are carried out in two stages, namely socialization activities, and mentoring. ICT-based learning does not always have advantages but also disadvantages in its application. One of the applications of ICT in learning is the use of learning media that can improve the quality of students' abilities. Multimedia-based learning such as technology that involves text, images, sound and video can present subject matter that is more interesting, not monotonous, and facilitates delivery. Through mentoring activities, the development of ICT-based learning prepared by teachers can improve its quality, so that the learning process is in line with the demands of skills according to the development of the times based on science and technology. The use of the internet in the world of teaching will help the world of teaching increase the quantity of students. The results of PKM socialization and mentoring at SMA Taman Rama Denpasar, resulted in outcomes and achievement targets 1) The preparation of an ICT-based Learning Implementation Plan (RPP) for each subject. 2) certificates for teachers who participate in socialization and mentoring.